Computerized measurement of melanocytic tumor depth in skin histopathological images. (October 2015) - Noroozi, Navid; Zakerolhosseini, Ali
Highlights: A method for computer assisted measurement of tumor depth is proposed that eliminates the drawbacks of the previously presented work in this field. The method provides the pathologists a second consultative opinion in evaluating histopathological samples. In this algorithm, active contours, convergence index filter and Fourier feature are used for detection of malignant melanocytes. Experimental results indicate that the method performs well in automated measurement of tumor invasion depth. Abstract: Measuring the tumor depth of invasion in skin tissue is of great importance for decision making in treatment of melanoma. Traditionally, measuring the tumor depth is based on the examination of histopathological slides by pathologist under the microscope which is time consuming and prone to intra and inter observer variability. In this paper, we propose a method for computer assisted measurement of tumor depth. At first, cornified layer is segmented based on entropy of the ridges detected in the image. Then, segmentation of cells nuclei is done using color features and active contour model. Melanocytes are distinguished from lymphocytes by applying convergence index filter and Fourier feature extraction. Experimental results indicate that the method performs well in automated measurement of tumor invasion depth.